2030 AD. Future Projections for Sustainable Design (diségno, 2023)
The International Conference 2030 AD. Future projections for sustainable design, which was held in Messina from 17 to 19 November 2022, obviously draws its reference from the ONU Agenda which, to the 17 objectives that embrace fundamental issues for sustainable development such as ending poverty, combating inequality and tackling climate change, adds a fourth theme concerning Living, as an articulated concept that underlies and interprets each attempt to act on any declination of sustainable development. [read more]